La vie scolaire comme espace d'éducation entre 1960 et 1968 : liberté, conformité, neutralité ? - Céline Chauvigné
The French school system and its traditional form of schooling (Vincent, 1980) were somewhat disrupted when the school was opened up to a larger number of pupils in a bid to democratise and then massify it, making order, discipline and the whole educational system an obsolete vision (Prost 2007) that could no longer suit the new public eager for freedom and to assert itself as a subject of law. In this context, the appearance of a counter-model, in the form of a heterotopia (Foucault, 1967), school life makes its comeback in the school as a space for life and compensation outside the classroom, which remains the central element of a conception of the French school. How then can these two models be reconciled within the narrow confines of the school form? How can this new deal, in its opposition to certain orientations of the Ferry republican school, find its place in the educational system? Through a study of the content (Bardin 2007) of a professional journal on school life, we propose to revisit the ideological project of the school, to observe and analyse the possible place of a life and commitment of pupils within secondary schools